Development and application of methods for determination of residual monomer in dental acrylic resins using high performance liquid chromatography - Urban, V. M.; Cass, Q. B.; Oliveira, R. V.; Giampaolo, E. T.; Machado, Ana Lucia [UNESP] (Wiley-Blackwell, 2006)
Two high-performance liquid chromatographic methods for determination of residual monomer in dental acrylic resins are described. Monomers were detected by their UV absorbance at 230 nm, on a Nucleosil((R)) C-18 (5 mu m particle size, 100 angstrom pore size, 15 x 0.46 cm i.d.) column. The separation was performed using acetonitrile-water (55:45 v/v) containing 0.01% triethylamine (TEA) for methyl methacrylate and butyl methacrylate, and acetonitrile-water (60:40 v/v) containing 0.01% TEA for isobutyl methacrylate and 1,6-hexanediol dimethacrylate as mobile phases, at a flow rate of 0.8 mL/min. Good linear relationships were obtained in the concentration range 5.0-80.0 mu g/mL for methyl methacrylate, 10.0-160.0 mu g/mL for butyl methacrylate, 50.0-500.0 mu g/mL for isobutyl methacrylate and 2.5-180.0 mu g/mL for 1,6-hexanediol dimethacrylate. Adequate assay for intra- and inter-day precision and accuracy was observed during the validation process. An extraction procedure to remove residual monomer from the acrylic resins was also established. Residual monomer was obtained from broken specimens of acrylic disks using methanol as extraction solvent for 2 h in an ice-bath. The developed methods and the extraction procedure were applied to dental acrylic resins, tested with or without post-polymerization treatments, and proved to be accurate and precise for the determination of residual monomer content of the materials evaluated. Copyright (c) 2005 John Wiley & Sons, Ltd.
Keywords: residual monomer; acrylic resins; HPLC; method validation; polymerization reaction